(untitled) (LSP International Journal, 2017)
The advancement of information and communication technology has greatly supported the promotion of tourism destinations. Arguably, the most popular and effective method of promotion is through websites or blogs. Hence, along with the growth of tourism is the development of tourism websites as the main resource for assessing information about the potential destinations. By focusing on the official tourism website of Malaysia, this paper attempts to investigate how the website portrays the diversity of culture, destinations and architecture of the country. Adopting a multimodal discourse approach, analysis was carried out on both language and visual elements. It is revealed that both these resources are strategically utilised to portray the diversity of Malaysia in an attempt to attract potential tourists.